2011
DOI: 10.1002/ddr.20455
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic opportunities in dengue infection

Abstract: Infection by one of the four serotypes of the arthropod-borne dengue virus produces a spectrum of disease manifestations, ranging from asymptomatic to life-threatening Dengue hemorrhagic fever/Dengue shock syndrome (DHF/DSS). During the last several decades, dengue has spread its geographic distribution to become the most common arboviral infection of humans in the subtropical and tropical regions of the world. There is no specific treatment or vaccine approved for human use. This fact, associated with the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 176 publications
(221 reference statements)
1
14
0
Order By: Relevance
“…Several studies in mice and humans have noted higher levels of viremia in severe dengue disease, which supports the assertion that increased viral replication is associated with more severe disease manifestation [17][21]. However, we and other groups have also demonstrated that inflammatory response, characterized by cytokine storm, also plays a fundamental role in dengue pathogenesis [7], [22][29]. Most of these studies were first characterized in a model of dengue infection using a mouse-adapted DENV-2 strain that mimics several clinical parameters seen in human disease, without affecting the CNS [22], [24][28].…”
Section: Introductionsupporting
confidence: 84%
“…Several studies in mice and humans have noted higher levels of viremia in severe dengue disease, which supports the assertion that increased viral replication is associated with more severe disease manifestation [17][21]. However, we and other groups have also demonstrated that inflammatory response, characterized by cytokine storm, also plays a fundamental role in dengue pathogenesis [7], [22][29]. Most of these studies were first characterized in a model of dengue infection using a mouse-adapted DENV-2 strain that mimics several clinical parameters seen in human disease, without affecting the CNS [22], [24][28].…”
Section: Introductionsupporting
confidence: 84%
“…At present, however, there are few preventative antiviral drugs or vaccines against dENV infection. Therefore, effective therapeutics and/or prophylaxis against dENV infection are urgently required (8).…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as an acute systemic viral infection transmitted to humans by Aedes mosquitoes, with a wide spectrum of clinical presentations, varying from an asymptomatic or a self-limited illness, called dengue fever (DF), to the potentially lethal forms, dengue hemorrhagic fever and dengue shock syndrome (DHF/Dss) [1][2][3]. Bhatt and colleagues showed using updated cartographic approaches that there are approximately 390 million dengue infectious cases per year around the world, of which 96 million manifest some level of disease severity [4].…”
Section: Introductionmentioning
confidence: 99%
“…the pathogenesis of Denv infection remains poorly understood and involves a complex interplay between viral and host factors [1,2,8]. severe forms of disease can be seen during primary infections [9,10]; however, epidemiological and observational studies demonstrate that the majority of DHF/Dss cases occur predominantly in either individuals with secondary heterologous Denv infections or in infants born from Denv-immune mothers [5,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation